Customer Relationship Marketing, Customer Bonding, and Customer Satisfaction on Customer Loyalty in Telecommunication Companies - Maupa, Haris; Cokki, Cokki; Sulaiman, Syarifuddin (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
The telecommunications industry is one of the most competitive industries with high penetration of digital technology, faster availability of data services, and innovations in telecommunications. The purpose of the present study is to empirically test a model that illustrates how customer relationship marketing (CRM) and customer bonding (CBD) affect customer loyalty (CLA) with customer satisfaction (CSA) as a mediating variable in the telecommunication company. A survey of the telecommunication customers was conducted with responses from 230 samples by maximizing the Partial-Least-Square Structural-Equation Modeling (PLS-SEM). The research results show that CRM and CBD are inferred to impact CLA and mediate CSA significantly. Compared to CRM, CBD has emerged as the most influential determinant of the proposed model. Marketing managers can adopt relevant business strategies and promote customer relationship marketing and customer bonding to achieve customer loyalty.